2016
DOI: 10.1155/2016/5609734
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exposure to Fenitrothion on Vital Organs in Rats

Abstract: This study was designed to investigate the impact of oral administration of fenitrothion (10 mg/kg) on liver, kidney, brain, and lung function in rats. The effect was studied on days 7, 14, 21, 28, and 42. Our results have shown deterioration in liver function as evidenced by the elevation in serum ALT, AST, ALP, and bilirubin and reduction in albumin and hepatic glycogen. This was associated with a state of hyperglycemia and hyperlipidemia and increased prothrombin time, while hemoglobin content was reduced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 91 publications
2
17
0
Order By: Relevance
“…Our study revealed that SUM led to an increase in serum uric acid and creatinine related to rats that received SUM-HPPJ and the control group, suggesting a kidney functional dysfunction. Our findings are consistent with other reports that confirmed that the kidney was one of the OPs target organs [47,65]. Honey has been shown to improve renal function in normal people by elevating nitric oxide levels and reducing prostaglandins [66].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study revealed that SUM led to an increase in serum uric acid and creatinine related to rats that received SUM-HPPJ and the control group, suggesting a kidney functional dysfunction. Our findings are consistent with other reports that confirmed that the kidney was one of the OPs target organs [47,65]. Honey has been shown to improve renal function in normal people by elevating nitric oxide levels and reducing prostaglandins [66].…”
Section: Discussionsupporting
confidence: 93%
“…The current findings revealed that administering fenitrothion induced homeostasis of glucose, as confirmed by a substantial gradual rise in the blood glucose level. Furthermore, previous research suggested that repeated exposure to OPs causes hyperglycemia and glycogen depletion in the muscle and liver [48,65]. This may be due to the impaired transport of glucose and the synthesis of glycogen [80].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the studies, we chose fenitrothion (FN), a synthetic insecticide from the group of organophosphates, that despite its toxicity and latest withdrawal from sale by the law in European countries, is commonly used in food storage facilities in many countries worldwide. Moreover, FN is very well-studied for its chemical and physiological properties, as evidenced by numerous studies, including reports about its influence on insects [ 22 , 23 , 24 , 25 ], rodents [ 26 , 27 , 28 ], and humans [ 29 , 30 , 31 ]. Therefore, this pesticide is a good model for the tests of organophosphates’ toxicity.…”
Section: Introductionmentioning
confidence: 99%